2019
DOI: 10.1177/1073858419835447
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Neuroscience Knowledge to Teachers and Their Practice

Abstract: While neuroscience has elucidated the mechanisms underpinning learning and memory, accurate dissemination of this knowledge to teachers and educators has been limited. This review focuses on teacher professional development in neuroscience that harnessed the power of active-learning strategies and best educational practices resulting in increased teacher and student understanding of cognition and brain function. For teachers, the experience of learning a novel subject in an active manner enabled them to subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 62 publications
0
53
0
9
Order By: Relevance
“…This pilot project was designed to train a cadre of Liberian science teachers in the neurobiology of learning and memory, emotional processing and stress, and the etiology of epilepsy and PTSD using best pedagogical practices ( Darling-Hammond et al, 2017 ) and lessons designed for high school classrooms ( Dubinsky et al, 2019 ). In this two tiered plan, a visiting neuroscientist delivered a 2 weeks workshop for Tier I teachers who then adopted the material for the Liberian context, delivered a series of 1 week workshops and trained additional Tier II Liberian teachers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pilot project was designed to train a cadre of Liberian science teachers in the neurobiology of learning and memory, emotional processing and stress, and the etiology of epilepsy and PTSD using best pedagogical practices ( Darling-Hammond et al, 2017 ) and lessons designed for high school classrooms ( Dubinsky et al, 2019 ). In this two tiered plan, a visiting neuroscientist delivered a 2 weeks workshop for Tier I teachers who then adopted the material for the Liberian context, delivered a series of 1 week workshops and trained additional Tier II Liberian teachers.…”
Section: Methodsmentioning
confidence: 99%
“…Similar training-of-trainers models had been used in prior programs ( Kohrt et al, 2018 ). Tier I training occurred in August 2018, and was comparable to a successful neuroscience teacher PD program in the United States ( MacNabb et al, 2006b ; Roehrig et al, 2012 ; Dubinsky et al, 2019 ; Schwartz et al, 2019 ). Lessons plans and resources used in the workshop were drawn mainly from open internet neuroscience resources ( MacNabb et al, 2006a ; SFN, 2019 ), as recommended for educational improvement in Sub-Saharan Africa ( Wolfenden et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there appears to be a paucity of empirical studies examining the complexity of moving between neuroscience and education, and the application of neuroscience theories in formal educational settings (c.f. Dubinsky et al , 2019 for examples of teacher professional development workshops in neuroscience).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dubinsky and colleagues (2013) created BrainU © , a training program for in-service science teachers. They found that training improved knowledge and confidence in participants’ understanding of neuroscientific information, enhanced their pedagogy, gave them tools to help their students understand their learning, and supported better understanding of the factors that impact their pedagogical practice several years after completing the program (Dubinsky et al, 2019). However, there is still much work needed to develop educational neuroscience training as some have found that while training decreases belief in neuromyths, it does not eliminate them (Macdonald et al, 2017).…”
Section: Discussionmentioning
confidence: 99%